PENYELESAIAN SENGKETA TERHADAP PENGGUNAAN OBAT TRADISIONAL YANG MENGANDUNG BAHAN KIMIA BERBAHAYA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Hadena Hoshita, L. P.; Adiwati, - (Kertha Semaya : Journal Ilmu Hukum, 2013)
Consumer dispute is a dispute between consumer and businesses (public or private) about product, good and service. One of the example is the utilization of traditional medicine which contains chemical instrument and free to buy in society. It can’t let on and on. In this article will explain the solution of using traditional medicine which contains chemical instrument based on government law No.8, 1999 about consumer safety. The purpose of this article to determine the dispute resolution efforts undertaken by consumers in the use of traditional medicines that contain harmful chemicals. This article is also explained normatively in the government law No. 8, 1999, there are two solutions to cope with these disputes, in the court and mediation off the court.
Keywords: Dispute, Consumer, Traditional Medicine, Chemical Instrument